Unraveling bovin phylogeny: accomplishments and challenges - Bibi Faysal; Vrba Elisabeth S (BMC Biology, 2010)
Abstract The phylogenetic systematics of bovin species forms a common basis for studies at multiple scales, from the level of domestication in populations to major cladogenesis. The main big-picture accomplishments of this productive field, including two recent works, one in BMC Genomics, are reviewed with an eye for some of the limitations and challenges impeding progress. See Research article http://www.biomedcentral.com/1471-2164/10/177